9‐Month‐Old Infants Recognize Individual Unfamiliar Faces in a Rapid Repetition ERP Paradigm. (30th September 2015) - Peykarjou, Stefanie; Pauen, Sabina; Hoehl, Stefanie
Abstract : To investigate whether infants show neural signatures of recognizing unfamiliar human faces, we tested 9‐month‐olds ( N  =   31) in a rapid repetition ERP paradigm. Pictures of unfamiliar male and female faces (targets) were preceded either by a central attractor (Unprimed) or by a face (Primed). In the latter case, the prime faces were either identical to the target (Repeated) or not (Unrepeated). We compared processing of primed versus unprimed faces as well as processing of repeated versus unrepeated faces. Primed stimuli elicited decreased P1 amplitude, P1 latency and N290 amplitude, indicating categorical repetition effects very early during the stream of processing. For repeated relative to unrepeated faces, N290 latency was reduced. In addition, we observed an enhanced late positivity at occipital channels for unrepeated compared to repeated male faces, but no difference for female faces. Taken together, these results suggest that 9‐month‐olds categorize faces before discriminating them individually. Furthermore, infants' ability to recognize face identity seems to depend on familiarity with the given face category, as indicated by differences in brain responses to male and female faces.